Implementing the Merdeka Curriculum in History Learning: Its Impact on Student Learning Autonomy at a Senior High School in Indonesia - Rika Cahyani; Ganda Febri Kurniawan; Arif Purnomo; Em Sereyrath; Romadi Romadi (Indonesian Journal of History Education, 2025)
This qualitative descriptive study analyzes the implementation of the Merdeka Curriculum in history education at a senior high school in Rembang, Indonesia, and examines its impact on student learning autonomy. Data were collected through in-depth interviews, classroom observations, and document analysis involving 43 participants, including teachers and students. Findings indicate that while teachers’ planning stages were systematically aligned with national guidelines, inconsistencies arose during execution, particularly in differentiated instruction and local history integration. Despite these gaps, the curriculum demonstrated a positive influence on fostering student autonomy, especially among Phase E (Grade X) learners, who exhibited greater confidence, self-regulation, and initiative. The study underscores the need for comprehensive teacher professional development to ensure faithful curriculum enactment. It contributes to the discourse on contextual pedagogical reform in post-colonial educational settings, highlighting how curriculum redesign can promote autonomous learning in history education.